2022
DOI: 10.3390/biology11070956
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p16/Ki-67 Immunostaining, hTERC Amplification and Fibronectin in Predicting Cervical Cancer Progression: A Systematic Review

Abstract: Human papillomaviruses (HPVs) are common sexually transmitted infectious agents responsible for several anogenital and head and neck cancers. Cervical cancer (CC) is the fourth leading cause of death in women with cancer. The progression of a persistent HPV infection to cancer takes 15–20 years and can be preventable through screening. Cervical cytology (Pap smear) is the standard screening test for CC and precancerous lesions. For ASC-US and ASC-H lesions, a combination of Pap smear and HR-HPV analysis is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Meanwhile, hrHPV-positive cases are problematic and will continue to be a source of overdiagnoses and added costly diagnostic procedures until more specific biomarkers are introduced. Among liquid-based cervical cytological samples with mild squamous atypia, the use of p16/Ki-67 dual stain has been shown to be more specific than the hrHPV testing and cytology in detecting HSILs and carcinomas [61, 62]. Although the data are still limited, the p16/Ki-67 dual stain also appears to be useful in the diagnosis of endocervical glandular atypia [62].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, hrHPV-positive cases are problematic and will continue to be a source of overdiagnoses and added costly diagnostic procedures until more specific biomarkers are introduced. Among liquid-based cervical cytological samples with mild squamous atypia, the use of p16/Ki-67 dual stain has been shown to be more specific than the hrHPV testing and cytology in detecting HSILs and carcinomas [61, 62]. Although the data are still limited, the p16/Ki-67 dual stain also appears to be useful in the diagnosis of endocervical glandular atypia [62].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study found that modifying CAR-T cells to secrete heparinase enzyme could destroy the tumor matrix and improve tumor infiltration while increasing anticancer efficacy [ 160 ]. Fibronectin, an essential scaffold of the ECM, acted as a barrier between T cells and tumor cells, significantly affecting T cell infiltration [ 161 ]. Extra domain A (EDA) and extra domain B (EDB), two selectively spliced fibronectin exons, are overexpressed in most cancers but barely expressed in healthy tissues [ 162 ].…”
Section: Challenges and Strategies Of Act In Solid Tumorsmentioning
confidence: 99%
“…The most striking advantage of p16/Ki-67 dual staining is its heightened sensitivity for detecting CIN2+ or CIN3+ lesions, which are precursors of cervical cancer [61,64,67]. Studies have consistently indicated that the sensitivity of dual staining is markedly higher than that of traditional cytology.…”
Section: Study Outcomes On Dual Staining Efficacymentioning
confidence: 99%